Tanggung Jawab Pelaku Usaha Salon Kecantikan Terhadap Kerusakan Gigi Konsumen Dalam Pemasangan Behel - Nurlina Nurlina; H. Arba Arba (Fakultas Hukum Universitas Mataram, 2022)
This research has the purpose to find out the legal basis, the rights, and duties of the businessman of a beauty salon and the legal responsibility of the businessman against consumer tooth damages because of dental braces. The type of this research is empirical-legal study, the approach method in this study uses the statute approach, the conceptual approach, and the sociological approach. The result of this study showed that the beauty salon has no legality to install a dental brace, this contrasted with their rights and duties. The beauty salon legality is only for beauty care. Moreover, the general doctor practitioners have also no legality to install a dental brace, the dentist (orthodontist) is the only medic who has legality to install a dental brace. Consequently, the beauty salon in the installment of dental braces has been done the malpractice, it has no legality to install, and it is the default in contract categorical, and torts. The businessman of the beauty salon has committed torts, disobeyed against freedom of contract, disobeyed halal requirements, and disobeyed certain thing principles. Because of this, there is no responsibility for a beauty salon in the installment of dental braces, because the agreement is null and void.